IMPLEMENTASI MODEL MARS DAN MEDIA BAAMBOOZLE UNTUK MENINGKATKAN MOTIVASI DAN BERPIKIR KRITIS SISWA DI SDN BENUA ANYAR 8 BANJARMASIN - Nisvia, Rodhotun; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem being investigated is the low learning motivation and critical thinking skills of students on Mathematics loads. This is due to teaching learning processes that only go in the direction, students are less actively involved during learning, are unable to analyze and solve problems, as well as to conclude problems, lack of use of strategies, models, and media that support learning. The attempt to overcome this is through the use of the MARS learning model and the Baamboozle media. The aim of this study is to improve students' learning motivation and critical thinking skills. The findings used the type of Action Research Class and the research participants were class IV students of the year of study 2023/2024 at SDN Benua Anyar 8 Banjarmasin. The data selected is qualitative obtained from motivation observations, motivation lifts and observations of students' critical thinking skills. The findings indicated that the motivation of students at meetings I to IV progressed from the criteria of "A Few Students Highly Motivated" to "Almost All Students Highly Motivated”. The elevation of the learning motivation in meeting I to meeting IV progressed from the criteria of “Most of the Students Highly Motivated” to "Almost All Students Highly Motivated”. The critical thinking skills of students in meeting I up to meeting IV have increased from the criteria “Some Students Think Critically” to “All Students think Critically”. Based on these findings, the MARS model and Baamboozle media can be concluded to improve student learning motivation and critical thought skills.